SIX YEARS OLD ELEMENTARY SCHOOL STUDENT CHARACTER ENHANCEMENT THROUGH IMPLEMENTATION OF CHARACTER BUILDING BASED ON STOP MOTION ANIMATION - Edwita, Desy Safitri, Sri Nuraini, Taufik Rihatno, Ajat Sudrajat, Arita Marini, Apri Wahyudi (International Journal of Advanced Science and Technology, 2020)
This research was done using classroom action research aiming for enhancing student character through implementation of character building based on stop motion animation for 20 six years old students grade one at Guntur 09 public elementary school in Jakarta in Indonesia.  This research involved two cycles in implementing character building based on stop motion animation related to character education in teaching learning process, school culture, extracurricular activities, and through community involvement.  The result of study found that student character in cycle 1 and 2 arrived at 68.91 % and 82.88 %.  The conclusion of this research is that implementation of character building based on stop motion animation can enhance student student character for 20 six years old students grade one at Guntur 09 public elementary school in Jakarta in Indonesia.